Unfiltered Marketing - Denny, Stephen; Leinberger, Paul (Ascent Audio, 2020)
You can fake authenticity. But in this digitally saturated age, your customers will see through any misdirection. As we are constantly on our electronic devices, we have come to distrust curated media and traditional PR. Stephen Denny and Paul Leinberger have found that people now want to make their own decisions based on raw footage, real-time updates, and unfiltered livestreams. How, then, do marketing executives and others gain consumer trust? These Fortune 500 consultants present the answer in Unfiltered Marketing. Drawing on four years of global research, authors Denny and Leinberger have developed a comprehensive five-step process for successfully rehumanizing the digital brand experience and gaining customer loyalty. To follow it, companies must understand that consumers are (1) seeking control in an out-of-control world; and executives must rework their brand to be (2) unscripted, (3) in-process, and (4) in-context, in order to master (5) heroic credibility (brands standing by their philosophy and values). Abiding by these rules, businesses follow in the successful footsteps of brands like Patagonia, T-Mobile, Adidas, GoDaddy, and others.